2022
DOI: 10.1002/cbic.202100689
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Reduce the On‐Target Platelet Toxicity of Bcl‐xL Inhibitors: PROTACs, SNIPERs and Prodrug‐Based Approaches

Abstract: Apoptosis is a highly regulated cellular process. Aberration in apoptosis is a common characteristic of various disorders. Therefore, proteins involved in apoptosis are prime targets in multiple therapies. Bcl-x L is an antiapoptotic protein. Compared to other antiapoptotic proteins, the expression of Bcl-x L is common in solid tumors and, to an extent, in some leukemias and lymphomas. The overexpression of Bcl-x L is also linked to survival and chemoresistance in cancer and senescent cells. Therefore, Bcl-x L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 71 publications
(120 reference statements)
0
22
0
Order By: Relevance
“…[40] Also, the route of administration can play a vital role in enhancing the degradation efficiency, as was observed with other types of PROTACs when administered through intravenous and intraperitoneal injections. [40] The UV light used in these experiments has low tissue penetration and restricts light-controlled PROTACs to topical use, such as leukemia and skin cancers. Therefore, investigating other photoswitches and light sources will mitigate these issues.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[40] Also, the route of administration can play a vital role in enhancing the degradation efficiency, as was observed with other types of PROTACs when administered through intravenous and intraperitoneal injections. [40] The UV light used in these experiments has low tissue penetration and restricts light-controlled PROTACs to topical use, such as leukemia and skin cancers. Therefore, investigating other photoswitches and light sources will mitigate these issues.…”
Section: Discussionmentioning
confidence: 96%
“…However, selecting appropriate intermembrane transporters [37] or specific‐cell receptors (such as FOLR1 and HER2) for the guided delivery can address these issues [38,39] . Additionally, their conjugations with coenzymes (such as folic acid, pyridoxine) and antibodies could improve their cell selectivity and uptake [40] . Also, the route of administration can play a vital role in enhancing the degradation efficiency, as was observed with other types of PROTACs when administered through intravenous and intraperitoneal injections [40] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12: 220171 encapsulation [77]. In the future, inhibitor of apoptosis (IAP)-based PROTACs could also hold promise as senolytics [78], especially in the light of recent work reporting on the overexpression of some IAP members in senescence [62].…”
Section: Class I Senolytics: Directly Targeting Apoptosis Gatekeepersmentioning
confidence: 99%
“…Currently, structural optimization of PROTACs mainly focuses on the evaluation of the structure–activity relationship (SAR) for various size linkers [ 55 ]. Previous studies have also demonstrated that the linker’s length does not influence the target binding affinity but can instead have a major impact on cytotoxicity since longer linkers have been shown to be more toxic [ 60 ]. Conversely, PROTACs with longer linkers show increased efficiency in mediating target protein degradation during the ubiquitination process.…”
Section: Introductionmentioning
confidence: 99%